(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Transculturalism is defined as "involving embracing or extending over two or more cultures," according to the Merriam-Webster Dictionary. The practise of transculturalism encompasses all of the world’s cultures. In the year 1940, the Cuban anthropologist Fernando Ortiz Fernandez provided the first definition of the word "Transculturalism." This definition was taken from the essay "Nuestra America" written by Jose Marti. A researcher of Afro-Cuban heritage, Fernando Ortiz was able to articulate the process of cultural assimilation and change from one tradition to another during his time in Cuba. It is generally agreed that VS Naipaul is one of the most well-known expatriate authors who also has first-hand knowledge with colonial life. This research paper’s objective is to investigate the ways in which several novels by V.S. Naipaul address topics with transcultural identities, multi-culturalism, and the identity crisis experienced by immigrants. The study will primarily concentrate on the problems of identifying oneself in a transcultural setting that are experienced by immigrants.